The Moderating Role of Dividend Policy on The Influence of Liquidity, Profitability, Leverage, and Investment Opportunity Set Against Stock Return Registered in The Jakarta Islamic Index - Nailul Mufidah; Agus Sucipto (Media Ekonomi dan Manajemen, 2020)
Stock return is an advantage expected by the investor in the latter days to the number of funds he/she has invested. There are two factors that affect the stock return, namely external and internal factors. The purpose of this study is to analyze the moderating role of dividend policy in the relationship between liquidity, profitability, leverage, and investment opportunity set against the stock return. This research uses a descriptive quantitative method with the population is service companies registered in the Jakarta Islamic Index for 2014-2018 periods. By implementing a purposive sampling technique, this study ended-up with 7 service companies as a sample.Â  Moreover, data analysis is processed with partial least square analysis techniques using the Application WarpPLS 6.0. The results showed that liquidity has significant negative impact on the stock return, profitability and investment opportunity set significantly positively affect the stock return, and leverage has no significant effect on stock return. While the dividend policy strengthens the liquidity relationship to stock return, the dividend policy weakens the leverage relation to the stock return, otherwise, the dividend policy is unable to moderate the profitability relationship and investment opportunity set against the stock return.